Strain engineering of topological properties in lead‐salt semiconductors. Issue 12 (7th October 2013) - Barone, Paolo; Di Sante, Domenico; Picozzi, Silvia
Abstract Rock‐salt chalcogenide SnTe represents the simplest realization of a topological insulator where a crystal symmetry allows for the appearance of surface metallic states. Here, we theoretically predict that strain, as realized in thin films grown on (001) substrates, may induce a transition to a topological crystalline insulating phase in related lead‐salt chalcogenides. Furthermore, relevant topological properties of the surface states, such as the location of the Dirac cones on the surface Brillouin zone or the decay length of edge states, appear to be tunable with strain, with potential implications for technological devices benefiting from those additional degrees of freedom. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)